2019
DOI: 10.26418/protobiont.v8i3.36965
|View full text |Cite
|
Sign up to set email alerts
|

Keanekaragaman Serangga Di Kawasan Iuphhk-Hti Pt. Muara Sungai Landak Kabupaten Mempawah Kalimantan Barat

Abstract: Insect is a dominant group of animals on earth with the most common number of species and individuals compared to other animal groups. Research about insect diversity in the forest area of IUPHHK-HTI PT. Muara Sungai Landak in swamp peat forest should be done to know its role. The research was aimed to determine the species of insects and to know the effect of environmental factors to insects in the area of PT. Muara Sungai Landak. Insects collected from five different age groups of plants with trapping method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…However, regression analysis found that temperature factors did not affect the diversity and abundance of beetles. It is because temperature and environmental factors influence the abundance and diversity of insects if sampling is carried out for a long time and in different seasons (Ricco et al, 2019). The population of Paederus beetles will increase at the end of the rainy season and then decrease after the dry season.…”
Section: The Effect Of Cultivation Methods On the Diversity And Abund...mentioning
confidence: 99%
“…However, regression analysis found that temperature factors did not affect the diversity and abundance of beetles. It is because temperature and environmental factors influence the abundance and diversity of insects if sampling is carried out for a long time and in different seasons (Ricco et al, 2019). The population of Paederus beetles will increase at the end of the rainy season and then decrease after the dry season.…”
Section: The Effect Of Cultivation Methods On the Diversity And Abund...mentioning
confidence: 99%
“…Keanekaragaman merupakan sifat komunitas yang memperlihatkan tingkat keanekaragaman jenis orgaisme yang ada di dalamnya (Ricco et al, 2019). Indeks keanekaragaman berfungsi untuk megetahui keanekaragaman biologi yang dipelajari didasarkan pada gagasan bahwa lebih banyak keanekaragaman dan kurangnya dominansi oleh satu atau lebih spesies berarti indeks keanekaragaman memiliki nilai yang lebih tinggi.…”
Section: Serangga Dan Arthropoda Lainnyaunclassified